Finance and Housing Provision in Portugal - Santos, Ana C. (2015)
In the last forty years, Portugal has experienced an extraordinary quantitative and qualitative transformation in housing provision, reflecting the rapid urbanisation of the country. These transformations were guided by a construction boom fuelled by rising mortgage debt resulting in a significant rise of homeownership. The paper analyses these changes through a Systems of Provision (SoP) approach, examining the interests, actions and interactions between different agents and how these have determined the dynamics and outcomes of the Portuguese housing SoP. It is argued that the financialisation of the Portuguese economy is central to account for the dynamics and specificities of the housing sector. Finance is an integral part of the boom in the second half of the 1990s and of the slow burn crisis since the turn of the millennium. The financialisation of the Portuguese housing SoP has had very mixed impacts both on production and consumption. In the construction sector, asymmetry is visible between small contracting companies and big companies, with the latter taking advantage of the possibilities opened up by eased access to external finance, expanding their activities to new national and international markets. It has also contributed to the amplification of inequalities between those included and excluded from the mortgage markets, as housing loans have been heavily concentrated on the better-off segments of the Portuguese population, which has not experienced a housing bubble like some of their European counterparts, accessing to new homes at affordable prices while at the same time accumulating wealth.